Dopamine DRD4 gene polymorphism as a risk factor for epilepsy in autism spectrum disorder - Mariane Wehmuth; Sérgio A Antoniuk; Karine Bittencourt da Silva; Salmo Raskinb; Adriana de Oliveira Christoff; Henrique Ravanhol Frigeri; Suelen Lucio Boschen de Souza; Liya Regina Mikami; Lilian Pereira Ferrari (Journal of Biology and Medicine - Peertechz Publications, 2020)
Background: Epilepsy can co-occur in Autism Spectrum Disorder (ASD) patients and impact the individual's behavior, socialization, and language development. Polymorphisms in the dopamine D4 receptor gene - DRD4 - have been studied as a potential biomarker for co-occurrence and severity of these disorders. In this study, we evaluated the prevalence of the polymorphisms of the DRD4 gene, its effects on clinical characteristics of ASD, and its association with epilepsy in ASD patients. Clinical investigations of 53 ASD patients aged between 2 and 16 years old were conducted to assess their health history and comorbidities. Genotyping of these patients was performed through the molecular analysis of the DRD4 gene polymorphisms.  Results: ASD and control subjects did not differ in the prevalence of DRD4 gene polymorphisms. However, heterozygous samples for DRD4 polymorphism of 7 repetitions presented greater association with epilepsy. Combining homozygous and heterozygous samples for DRD4 polymorphism of 7 repetitions resulted in no significant difference. The relative risk for epilepsy in heterozygous for DRD4 polymorphism with 7 repetitions increased 3.5-fold. Conclusion: ASD patients with DRD4 gene polymorphism of heterozygous alleles with 7 repetitions are associated with a higher frequency of epilepsy.